ANALISIS POTENSI LIKUIFAKSI DI AREA PLTU PACITAN - Mesra Srya Ariefin; Arief Rachmansyah; As’ad Munawir (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
One of Indonesia's regions, Pacitan, is an earthquake-prone area where one of the consequences of the earthquake is the phenomenon of soil liquefaction. Soil liquefaction is the process of changing or transforming the form from a solid to a liquid form. The purpose of this study was to analyze the potential for liquefaction based on field data at the finite element PLTU Sudimoro Pacitan or FEM method. There are three location plans for the liquefaction potential analysis point, namely C-36, S-58, and TC-32 based on earthquake data. Point C-36 has the possibility of liquefaction. For the point S-58 has conditions that will definitely experience liquefaction. Meanwhile, Point TC-32 has the possibility of liquefaction. The subsidence that occurs due to the earthquake load has a large enough impact on land subsidence, namely at point C-36